The classroom culture of a middle school music technology class. (August 2020) - Albert, Daniel J.
The purpose of this study was to examine the culture of an American middle school music technology classroom based in musical composition. Research questions explored students' perceptions of how they co-create the classroom culture with the teacher and how the classroom culture influences participation in musical composition activities, if at all. Data sources for this ethnographic case study included field notes from multiple class observations, audio- and video-recordings, and semi-structured interviews. Findings determined that teacher and students' mutual use of constructive feedback in their discourse, the teacher's role as co-learner, his facilitation of "messiness" as part of the learning process, and his pedagogical style helped to create an affirming classroom culture that motivated students to compose. Implications for teaching practice include critical examination of classroom cultures and thoughtful inclusion of technology in music education courses.